Estudio de prefactibilidad del montaje del centro distrital de resonancia magnética de Bogotá (2014)
The Degree Work presented below corresponds to the Pre-Feasibility Study for the Assembly of the District Resonance Center in Bogota, which is part of the Specialization of Development and Integral Project Management of the Colombian School of Engineering July Garavito and includes the stages of Identification and Strategic Alignment of the Project (IAEP), Formulation and Evaluation of the Project.